Women as Objects of Sexual Harassment on Social Media X (A Case Study of Account X @amndzahra) - Wiyono, Dwi Shadillah Talentania Putri; Wibowo, Arif Ardy; Nasir, Roziani (INJECT (Interdisciplinary Journal of Communication), 2024)
The phenomenon of digital and social media has increasingly raised attention to sensitive social issues, including the case of Amanda Zahra who became a victim of sexual harassment. This research uses a descriptive qualitative approach with a case study analysis method to examine the phenomenon of sexual harassment that occurs on X @amndzahra’s social media account using Muted Group Theory as the theoretical basis for this research. The data collection techniques used include non-participatory observation and documentation. The results showed that Amanda Zahrah as a victim of sexual harassment faced difficulties to articulate their discomfort caused by the existence of language dominated by masculine views and social structures that limit women’s participation can affect their ability to voice traumatic experiences effectively.